Kierkegaard and Schmitt on the State of Exception - Neoh, Joshua (Journal of law and religion, 2024)
This essay begins with a quotation from Carl Schmitt in which he quotes Søren Kierkegaard on the significance of the exception in political theology. The essay is an extended reflection on this quotation within a quotation. Through a comparison of Kierkegaard and Schmitt, the author presents two readings of the state of exception: the first centers on the figure of the sovereign, while the second centers on the figure of the martyr. The sovereign suspends the law from above, while the martyr suspends it from below. In the political sphere, there are two ways of becoming the exception: the sovereign versus the martyr.